The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.2041-1014.2010.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of human aortic endothelial cells by oral viridans group streptococci and induction of inflammatory cytokine production

Abstract: Oral viridans group streptococci are the major commensal bacteria of the supragingival oral biofilm and have been detected in human atheromatous plaque. Atherosclerosis involves an ongoing inflammatory response, reportedly involving chronic infection caused by multiple pathogens. The aim of this study was to examine the invasion of human aortic endothelial cells (HAECs) by oral viridans group streptococci and the subsequent cytokine production by viable invaded HAECs. The invasion of HAECs by bacteria was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 35 publications
7
52
1
Order By: Relevance
“…S. aureus forms vegetations by adhering to the endothelial cell surface and subsequently aggregating in the presence of plasma (34). Recently, viridans group streptococci have been reported to display properties of adhesion to and invasion of human vascular endothelial cells (35,36). S. mutans, classified as a viridans group streptococcus, also showed properties of high levels of adhesion to endothelial cells, which was mainly observed in CBP-positive S. mutans strains, with the distribution of such strains being approximately 10 to 20% of all S. mutans strains (9,21).…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus forms vegetations by adhering to the endothelial cell surface and subsequently aggregating in the presence of plasma (34). Recently, viridans group streptococci have been reported to display properties of adhesion to and invasion of human vascular endothelial cells (35,36). S. mutans, classified as a viridans group streptococcus, also showed properties of high levels of adhesion to endothelial cells, which was mainly observed in CBP-positive S. mutans strains, with the distribution of such strains being approximately 10 to 20% of all S. mutans strains (9,21).…”
Section: Discussionmentioning
confidence: 99%
“…27 A recent survey showed that oral viridans group streptococci are capable of invading human aortic endothelial cells and triggering the production of inflammatory cytokines and monocyte chemoattractant proteins. 28 Thrombogenic properties of viridans streptococci have also been investigated. Oral streptococci may initiate or contribute to platelet aggregation in coronaries.…”
Section: Discussionmentioning
confidence: 99%
“…(7,21) However, it appears that oral hygiene involving 2% chlorhexidine and toothbrushing alone does not prevent VAP in heterogeneous populations of severely ill, intubated patients and thus should be performed in combination with other preventative measures. (10) One such set of preventative measures reduced pneumonia in 89.7% of the studied patients.…”
Section: Discussionmentioning
confidence: 99%